THEORETICAL AND LEGAL PRINCIPLES OF RESTRICTION OF HUMAN AND CITIZEN RIGHTS UNDER MARTIAL STATE CONDITIONS - Holovko, Pavlo (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to determine the theoretical and legal principles of the implementation of restrictions on human rights in martial law. Research methods: analytical and generalizing, structural and semantic, syntactic, comparative, classification, etc. Results: the relevance of the issues of theoretical principles and practical ways of legal support for temporary restrictions on individual human rights in martial law is determined. The distinction between the content of the concepts of restriction of rights and deprivation of rights is attributed to an important fundamental aspect of the theoretical basis of the specified problem and the criteria for such a distinction are proposed. The results of studies of the problem of restriction of human rights in martial law or emergency carried out by foreign and domestic scientists are summarized. The prospects of the derogation model, which is considered as a state response to an emergency situation and is characterized by a partial departure of the state from obligations, while remaining within the law, are substantiated. Discussion: it is indicated that the restriction of rights is considered by jurisprudence as a legitimate manifestation of the state’s function of balancing the interests of the individual and society in conditions of emergency or martial law, and the deprivation of rights is a form of legal responsibility or sanction that completely removes the relevant right from the legal status of the individual. It is noted that foreign researchers primarily study the issue of temporary restriction of human rights in conditions of crisis or emergency, while national jurisprudence actively studies the specified problem, focusing specifically on the conditions of martial law, while maintaining a strong relationship between the specified approaches. The requirement for derogation in terms of compliance with the standards of necessity, proportionality, predictability and legality and extension only to individual rights that are clearly defined by legislation is emphasized.